Search for the Standard Model Higgs boson decay to μ+μ− with the ATLAS detector - Aad, G. (2014)
A search is reported for Higgs boson decay to μ+μ− using data with an integrated luminosity of 24.8 fb−1 collected with the ATLAS detector in pp collisions at s√=7 and 8 TeV at the CERN Large Hadron Collider. The observed dimuon invariant mass distribution is consistent with the Standard Model background-only hypothesis in the 120-150 GeV search range. For a Higgs boson with a mass of 125.5 GeV, the observed (expected) upper limit at the 95 % confidence level is 7.0 (7.2) times the Standard Model expectation. This corresponds to an upper limit on the branching ratio BR(H→μ+μ−) of 1.5×10−3.